Penerapan Teknologi Tepat Guna Alat Penabur Pupuk Urea di Desa Montor - Saipullah Zainal Muttaqin; Ratu Diana Safitri; Nadia Mardotilah; Muhammad Fathul Farhi (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
This community service activity was conducted in Montor Village with the aim of introducing and applying appropriate technology in the form of a urea fertilizer spreader. This program was driven by the problems faced by farmers, such as inefficiency in time and labor, and health risks caused by the manual fertilization method that requires a bent posture. In this activity, KKM students not only provided socialization but also held a participatory workshop to build the fertilizer spreader with the villagers using locally available materials such as pipes. The results of this program showed that the farmers realized that the fertilization process could be done more efficiently, quickly, and ergonomically. The fertilizer spreader produced proved to reduce physical fatigue, speed up work time, and ensure more uniform fertilizer distribution. This activity successfully raised awareness among farmers about the importance of simple innovations in agriculture and strengthened collaboration between students and the community in solving local agricultural problems. The success of the fertilizer spreader demonstrates the significant potential of appropriate technology in improving farmers' efficiency and work quality, as well as promoting sustainability in the agricultural sector in rural areas.